2012
DOI: 10.1260/0263-6174.30.8-9.773
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Separation of Isomaltooligosaccharides on Ion-Exchange Resins: Effect of the Cationic Form

Abstract: Prebiotic isomaltooligosaccharides (IMOs) are composed of α-Dglucose units linked by glucosidic α (1∅6) bonds and they remain intact until reaching the large bowels, where they are metabolized by bifidobacteria and lactobacillus. These saccharides can also be synthesized enzymatically, wherein the reaction media is composed of monosaccharides (glucose and fructose), disaccharides (sucrose and maltose), IMOs (the product of interest) and dextrans. Dextrans are readily separated by solvent precipitation; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The strength of the formed cation–sugar complexes determines the degree of sugar adsorption, which is dependent on the number and orientation of the OH groups, and also the hydration and ionic radius of the counterion (Havlicek & Samuelson, 1975; Jones et al., 1960). It was reported that the strongly acidic cation‐exchange resins in different cationic forms (H + , Na + , K + , and Ca 2+ ) all preferentially adsorb monosaccharides (e.g., glucose and fructose) over disaccharides (e.g., sucrose and maltose) and IMOs with higher DP (Rabelo et al., 2012), which is mainly attributed to the size exclusion effect. A similar adsorption study was conducted on GOS (Wisniewski et al., 2014).…”
Section: Purification and Fractionation Of Glcosmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the formed cation–sugar complexes determines the degree of sugar adsorption, which is dependent on the number and orientation of the OH groups, and also the hydration and ionic radius of the counterion (Havlicek & Samuelson, 1975; Jones et al., 1960). It was reported that the strongly acidic cation‐exchange resins in different cationic forms (H + , Na + , K + , and Ca 2+ ) all preferentially adsorb monosaccharides (e.g., glucose and fructose) over disaccharides (e.g., sucrose and maltose) and IMOs with higher DP (Rabelo et al., 2012), which is mainly attributed to the size exclusion effect. A similar adsorption study was conducted on GOS (Wisniewski et al., 2014).…”
Section: Purification and Fractionation Of Glcosmentioning
confidence: 99%
“…A similar adsorption study was conducted on GOS (Wisniewski et al., 2014). Both studies found that sulfonated PS‐DVB in the H + form showed the highest productivity and selectivity for oligosaccharides separation (Rabelo et al., 2012; Vente et al., 2005). The strongly basic anion exchange resins functionalized with quaternary ammonium groups have also been used for the separation of anionic and neutral oligosaccharides (Lee, 1996).…”
Section: Purification and Fractionation Of Glcosmentioning
confidence: 99%